Риторичні вправи як засіб формування комунікативної компетентності майбутніх учителів початкових класів - Гудима, Наталія; Hudyma, Nataliia (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті з’ясовано роль та місце риторичних вправ і завдань у процесі формування комунікативної компетентності майбутніх учителів початкових класів; розроблено систему вправ і завдань з риторики української мови, що сприяє опануванню риторичних відомостей і формуванню професійно важливих мовно-риторичних умінь студентів ОКР «бакалавр» напряму підготовки «Початкова освіта».The process of preparing future teachers for speech activity involves the formation of their communicative skills, which are the part of their identity and are important not only for successful professional activity, but also for participation in various spheres of life in the society. The article determines the role and place of rhetorical exercises and tasks in the process of developing communicative competence of primary school teachers. The author has worked out the system of exercises and tasks promoting the acquisition of basic knowledge in rhetoric and the formation of professionally important linguistic and rhetorical skills of the students-bachelors specialising in primary education. The practical classes in Basics of Rhetoric in Primary School facilitate development of the following students’ communicative skills: to conduct a monologue on professional topics; to conduct an effective, constructive conversation on any topic, using verbal and nonverbal means; to acquire the skills of the polemic art, to have background knowledge of ethical culture of constructive dialogue and polylogue (debate, polemics, discussion).
Rhetorical Exercises as a Means of Forming Future Primary School Teachers’ Communicative Competence
Keywords: риторика; риторичні вправи та завдання; риторичні вміння; комунікативна компетентність; учителі початкових класів; rhetoric; rhetorical exercises and tasks; rhetorical skills; communicative competence; primary school teachers